Keragaman makrozoobenthos di perairan Kuala Gigieng Kabupaten Aceh Besar - Nur Fadli; Ichsan Setiawan; Nurul Fadhilah (Depik, 2012)
Abstract. The objective of present study was to study the diversity of macrozoobenthos in Kuala Gigieng estuary, Aceh Besar. The study was conducted in June 2011. The random sampling method was used to determine the area and sampling points based on tidal activities. Samples were taken with the Eckmann grab, then identified at Marine Biological Laboratory of Marine Science Department. The results showed that there were three class of macrozoobenhos (Malacostraca, Gastropoda, and bivalves) within 12 species of makrozoobenthos occured in Kuala Gigieng. The Shannon-Wienner diversity index (H') at high tide, mean sea level, and low tide were 1.26, 1.446, and 1.892, respectively, and it was categorized as low level. Keywords. Diversity, Makcrozoobenthos, Gigieng estuary